Procedures for considering implementation disputes and its suspension in Saudi law - Al Harbi, Abdullah bin Masoud bin Marzouq (Journal of Economic, Administrative and Legal Sciences, 2018)
Executive disputes are cases arising out of the execution and are a prevention of its inhibitions and relate to the availability of the conditions of validity of the execution, such as the execution place, document or parties or procedures. Executive disputes are divided into several divisions based on several considerations. It is divided into objective disputes and temporary disputes. Also, some of disputes are before the start of execution, and some during of execution, and other after completion of execution. The importance of these divisions lies, in several matters, including: knowledge of state jurisdiction. For acceptance of the executive dispute in front of the enforcement judge it is required the capacity, interest and eligibility. It is also required to submit before Suspension of execution and has the capacity of urgency and temporary action. The researcher get a number of recommendations, including: • Reordering the special materials for stop execution. In which that they are in one place and have to arranged according to time and competence. • Transfer the Article (170) from the system of legal proceedings to the execution system. • The regulator shall provide for the condition of capacity and eligibility to accept the execution dispute in particular and to accept the judicial case in general. The curriculum used is the analytical inductive curriculum, which is in depend on the study of the regular article and its interpretation through the regulations and decisions. As well as reading orders and decisions and extracting the article in which had to follow it.